Occupational Safety and Health (K3), Work Environment and Competence on Employee Performance - Jumadil Hasman Nugraha; Masdar Mas’ud; Juliyanti Sidik Tjan (Manunggal Halim Jaya, 2025)
Research objectives (1) To determine the effect of occupational safety and health on employee performance; (2) To determine the effect of Work Environment on Employee Performance. (3) To determine the effect of Competence on Employee Performance. The type of research used in this study is quantitative research using primary data. The sample in this study was 60 respondents. The sampling technique used in this study was a survey method. Meanwhile, the analysis methods used in this study are data validity test, data reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, partial influence test (t-test), simultaneous influence test (F test) and simultaneous determination test R2 with the help of SPSS Version 25. The results of the study indicate that (1) Occupational Safety and Health has a positive and significant influence on Employee Performance at PT PLN (Persero) UP3 Kendari (2) Work Environment has a positive and significant influence on Employee Performance at PT PLN (Persero) UP3 Kendari. (3) Competence has a positive and significant influence on Employee Performance at PT PLN (Persero) UP3 Kendari